Investigating the Relationship between Occupational Stress and Job Satisfaction among University Faculty Members (Case Study: A University in Tehran) - Adel Shokri; Tooraj Dana; Amirhooman Hemmasi; Solmaz Toutounchian (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The current research aims to determine job stress and satisfaction among university faculty members in Tehran and investigate the relationship between these two indicators.Methodology: This research is among the cross-sectional, descriptive, and analytical studies. The sample consisted of 52 faculty members of a university in Tehran province whose names were not disclosed due to confidentiality. The research instruments include a personal-job information questionnaire, a job satisfaction questionnaire, and the Steinmetz Job Stress Survey. Descriptive and inferential statistics were used for data analysis.Findings: The results indicate a significant negative correlation between job satisfaction and job stress among faculty members, meaning that as job satisfaction increases, stress decreases and vice versa. Job satisfaction among faculty members was moderate. Additionally, faculty members, direct supervisors, and colleagues were significantly satisfied with the nature of their work, while they were significantly dissatisfied with their salaries and benefits. Job stress among faculty members was relatively low. Full professors had higher job satisfaction than associate professors.Originality/Value: University faculty members significantly shape the culture and advance knowledge for future generations. Therefore, efforts should be made to enhance job satisfaction and reduce stress. By implementing identified strategies, organizational excellence in universities should be facilitated through attention to human resources, which are considered national assets.